Bangladesh Rural Income Diagnostic : Enabling Faster and More Equal Income Growth in Rural Bangladesh - Genoni, Maria Eugenia; Ahmed, Md Mansur; Gautam, Madhur; Tillan, Pablo Antonio (Washington, DC: World Bank, 2022)
This Rural Income Diagnostic (RID) aims to answer the question: “What are the main opportunities and constraints to faster, sustained income growth for poor and vulnerable households in rural Bangladesh” This analysis is motivated by recent evidence highlighting the centrality of rural areas for poverty reduction in Bangladesh and the need to update our understanding of rural income dynamics to better inform policy solutions. The objective of the analysis is to inform the World Bank Systematic Country Diagnostic and governmentplanning. The analysis focuses on areas where progress can be made in the next five years, consistent with the country’s long-term development path. The focus on short-term priorities to accelerate rural income growth needs to be implemented in a manner that is consistent with, and does not distract from, long-run goals and investments that will have very high future returns, especially for the poor. These include investments in child nutrition, health, and education.